The Impact of Peer Behavior on Islamic Religious Education Achievement - Nurislamiah, Siti (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
Teachers' learning management skills and Peer behavior are considered crucial factors influencing student outcomes in Islamic Religious Education (PAI). Understanding their impacts can guide improvements in educational practices. This study investigates the effects of PAI teachers' learning management skills and peer behavior on students' PAI learning achievement at SMP PGRI 396 Kelapa Dua. The research examines whether these factors significantly influence students' academic performance in Islamic Education. This quantitative study utilizes a descriptive methodology, focusing on a sample of students from a total population. Data were collected through structured questionnaires and analyzed using SPSS. The study assessed teachers' learning management skills and peer behavior, examining their relationship with PAI achievement. Statistical analyses, including correlation tests, were conducted to evaluate significance. The findings reveal a significant relationship between peer behavior and PAI achievement, with a significance value indicating a correlation coefficient that explains a portion of the variance in PAI achievement. In contrast, PAI teachers' learning management skills did not show a significant impact. The results suggest that while peer behavior plays a role in influencing PAI learning outcomes, other factors may contribute more significantly, warranting further investigation into additional variables.